Microcavity-Enhanced Light-Trapping for Highly Efficient Organic Parallel Tandem Solar Cells - Zuo, Lijian; Chueh, Chu-Chen; Xu, Yun-Xiang; Chen, Kung-Shih; Zang, Yue; Li, Chang-Zhi; Chen, Hongzheng; Jen, Alex K.-Y. (Advanced materials (Weinheim), 2014)
A high‐performance parallel tandem solar cell employing ultra‐thin Ag as the intermediate anode is demonstrated, which comprises a semitransparent front sub‐cell and a microcavity assisted back sub‐cell. In addition to the extended optical field as a result of the tandem architecture, the prominent microcavity resonance formed in the back sub‐cell enables such a parallel tandem configuration to possess high light utilization efficiency (the peak EQE value is over 80%) and a high photovoltaic performance of 9.2%. This study establishes an effective architecture that can be generally applicable to all organic materials for improving their performance.